Associations between very low concentrations of low density lipoprotein cholesterol, high sensitivity C-reactive protein, and health outcomes in the Reasons for Geographical and Racial Differences in Stroke (REGARDS) study. (28th August 2018) - Penson, Peter E; Long, D Leann; Howard, George; Toth, Peter P; Muntner, Paul; Howard, Virginia J; Safford, Monica M; Jones, Steven R; Martin, Seth S; Mazidi, Mohsen; Catapano, Alberico L; Banach, Maciej
Abstract: Aims: Recent findings have demonstrated the important contribution of inflammation to the risk of cardiovascular disease (CVD) in individuals with optimally managed low density lipoprotein cholesterol (LDL-C). We explored relationships between LDL-C, high sensitivity C-reactive protein (hs-CRP), and clinical outcomes in a free-living US population. Methods and results: We used data from the REasons for Geographical And Racial Differences in Stroke (REGARDS), and selected individuals at 'high risk' for coronary events with a Framingham Coronary Risk Score of ≥10% or atherosclerotic cardiovascular disease (ASCVD) risk ≥7.5% in order to explore relationships between low LDL-C [<70 mg/dL (1.8 mmol/L) in comparison to ≥70 mg/dL (1.8 mmol/L)]; hs-CRP <2 compared with ≥2 mg/L and clinical outcomes [all-cause mortality, incident coronary heart disease (CHD), and incident stroke]. To assess the association between the LDL-C and hs-CRP categories and each outcome, a series of incremental Cox proportional hazards models were employed on complete cases. To account for missing observations, the most adjusted model was used to interrogate the data using multiple imputation with chained equations (MICE). In this analysis, 6136 REGARDS high-risk participants were included. In the MICE analysis, participants with high LDL-C (≥70 mg/dL) and low hs-CRP (<2 mg/L) had a lower risk of incident stroke [hazard ratio (HR) 0.69, 0.47–0.997], incident CHD (HR 0.71, 0.53–0.95), and CHD death (HR 0.70, 0.50–0.99) than those in the same LDL-C category high hs-CRP (≥2 mg/L). In participants with high hs-CRP (≥2 mg/dL), low LDL-C [<70 mg/dL (1.8 mmol/L)] was not associated with additional risk reduction of any investigated outcome, but with the significant increase of all-cause mortality (HR 1.37, 1.07–1.74). Conclusions: In this high-risk population, we found that low hs-CRP (<2 mg/L) appeared to be associated with reduced risk of incident stroke, incident CHD, and CHD death, whereas low LDL-C (<70 mg/dL) was not associated with protective effects. Thus, our results support other data with respect to the importance of inflammatory processes in the pathogenesis of CVD.